The process of institutionalization of Anthropology in Peru and the invention of the Indian (1927-1960): O processo de institucionalização da Antropologia no Peru e a invenção do índio (1937 – 1960) (Revista de História da UEG (REVHIST), 2024)
When talking about Anthropology in Peru, it´s normally referred to as if it were uniform or that it came from a single founding trunk, when in reality it had diverse processes that deserve attention. The objective of this article is to explore forms of institutionalization that the first two anthropological institutions in Peru had: the Universidad Nacional San Antonio Abad del Cusco in 1942 and the Universidad Nacional Mayor de San Marcos in 1946. As well as in how these institutionalization processes affected and shaped the invention and conceptualization of its object of study, the Indian. Based on a bibliographic and institutional archive review, propose the comparison of both processes. Conclude that both processes of institutionalization of Anthropology depended on its position in the context of social research in Peru carried out by foreigners at the beginning of the 20th century and on the indigenous political debates that they collected. Elements that are also closely linked and give shape to their particular inventions of their object of study. Keywords: Indigenism; Anthropology; Object of study; institutionalization; indigenous.